Beyond Breakdown: Enacting Infrastructural Life with Augustin Daly's Under the Gaslight - O'Brien, Adam; Hofer-Robinson, Joanna; Kirkby, Nicola; Brice, Jeremy (GeoHumanities, 2025)
Alternation between mundane invisibility and spectacular foregrounding is a critical touchstone of infrastructural aesthetics. Infrastructure failures, which often mediate between these states, therefore attract disproportionate attention despite focusing scholarly enquiry on things that no longer function as infrastructure. This article seeks to escape this impasse through analysing cultural artefacts for evidence of processes which are inconspicuous but nevertheless constitute the happenings of infrastructure. Through close readings of Under the Gaslight (1867), a sensation drama which interweaves melodramatic narratives with infrastructural spaces and temporalities, we introduce three techniques for navigating the representational elusiveness of infrastructural processes and relations. We suggest that following fictional characters' engagements with infrastructures can disclose the experiential textures of mundane infrastructural functioning; that engaging with fiction across historical distance can induce states of alienation which defamiliarise infrastructural processes and render them spectacular; and that examining the infrastructural promises embedded in melodrama can foreground infrastructure's temporalities.